Rare earth smart nanomaterials for bone tissue engineering and implantology: Advances, challenges, and prospects - Duraipandy Natarajan; Zhitong Ye; Liping Wang; Linhu Ge; Janak Lal Pathak (Wiley, 2022)
Abstract Bone grafts or prosthetic implant designing for clinical application is challenging due to the complexity of integrated physiological processes. The revolutionary advances of nanotechnology in the biomaterial field expedite and endorse the current unresolved complexity in functional bone graft and implant design. Rare earth (RE) materials are emerging biomaterials in tissue engineering due to their unique biocompatibility, fluorescence upconversion, antimicrobial, antioxidants, and anti‐inflammatory properties. Researchers have developed various RE smart nano‐biomaterials for bone tissue engineering and implantology applications in the past two decades. Furthermore, researchers have explored the molecular mechanisms of RE material‐mediated tissue regeneration. Recent advances in biomedical applications of micro or nano‐scale RE materials have provided a foundation for developing novel, cost‐effective bone tissue engineering strategies. This review attempted to provide an overview of RE nanomaterials' technological innovations in bone tissue engineering and implantology and summarized the osteogenic, angiogenic, immunomodulatory, antioxidant, in vivo bone tissue imaging, and antimicrobial properties of various RE nanomaterials, as well as the molecular mechanisms involved in these biological events. Further, we extend to discuss the challenges and prospects of RE smart nano‐biomaterials in the field of bone tissue engineering and implantology.